From conflict to consensus: European neoliberalism and the debate on the future of EU social policy. (1st April 2010) - ,
Abstract : This paper focuses on the debate on EU social policy from the 1980s to the present. It argues that neoliberals have retained and extended their hegemony in a changing discursive setting. In the 1980s, neoliberal ideas clearly dominated but there was also an anti-neoliberal position calling for a stronger 'positive' social integration in Europe. From the 2000s onwards, however, the situation has changed. The debate on social integration has shifted from an antagonist constellation, where those in favour of positive market-correcting social integration opposed those in favour of a predominantly negative economic integration, to a consensual constellation, where it is seen as common sense that social issues are important so long as they improve competitiveness and are regulated only at a national level. Since anti-neoliberal arguments have lost their pervasive power, neoliberal hegemony has become even more thorough. Under this regime, opponents of the Lisbon strategy of European neoliberalism are forced to participate in fragmented conflicts in separate policy fields. This obliges them to comment on detailed policy questions rather than on major integration issues, thus losing the opportunity to debate the major lines of EU integration. The context for discussing EU social policy perspectives is now twofold: long-term political visions of EU social policy are treated within a neoliberal consensus; whilst the envisioning of short-term policy, relating to national social policies is treated in European policy fields regulated by the Open Method of Coordination. Ambitions that are directed both at market-regulating policies and at the European level, fall through the lattice of the Lisbon strategy.